A Convenient Synthesis of 4, 6-Dimethyl-2-(Methylsulfonyl)Pyrimidine. (December 2013) - Xu, Defeng; Zhu, Zhiling; Wang, Ziqiao
A convenient and efficient three-step synthesis of 4, 6-dimethyl-2-(methylsulfonyl) pyrimidine can be achieved by cyclocondensation of acetylacetone and thiourea in the presence of hydrochloric acid to yield 4, 6-dimethyl-1-merc aptopyrimidine, methylation with dimethyl carbonate and tetrabutylammonium bromide to give 4, 6-dimethyl-2-methyl thiopyrimidine, and oxidation with hydrogen peroxide, sodium tungstate and tetrabutylammonium bromide to afford the title compound in an overall yield of 75%.